Relation of Normal Childbirth Care Training to Midwives Knowledge and Attitudes at Bebesen Health Center Bebesen District of Central Aceh Regency in 2021 - Hasritawati; Barirah Madeni (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Background. Mortality and morbidity in pregnant and maternity women is a big problem in developing countries. In poor countries, about 25-50% of deaths of women of childbearing age are caused by pregnancy-related causes. It is estimated that every year 585,000 women die from pregnancy and childbirth. 99% of these deaths occur in developing countries. According to WHO, 60-80% of maternal deaths are caused by bleeding during childbirth, obstructed labor, sepsis, high blood pressure during pregnancy, and complications from unsafe abortion. The purpose of this study was to determine the relationship between normal delivery care (APN) training on the knowledge and attitudes of midwives at the Bebesen Health Center, Bebesen District, Central Aceh Regency in 2020. Methods. The research method uses an analytical survey method with a cross sectional approach, which is a study to study the dynamics of the correlation between risk factors and effects, by approaching, observing or collecting data at once. The population in this study was all 63 midwives. The sampling method uses a total sampling technique that uses all members of the population as a sample. Data collection was carried out from November 14-16, 2020. Results. The results showed that from the analysis obtained a value for the p-value of good knowledge as many as 20 respondents (31.7%) and a positive attitude that is as many as 32 respondents (50.8%). Conclusion. There is a relationship between normal delivery care training (APN) with knowledge with a p value of 0.014 (p < 0.05) and normal delivery care (APN) with changes in the attitude of midwives with a p value of 0.00 (p < 0.05) in Bebesen Public Health Center, Bebesen District, Central Aceh Regency.